Clarification on the Concept of Centrality Within Social Networks - Luqman Ahmad (Research Journal of Psychology, 2024)
In this article, the logical basis for measuring structural centrality in social networks is looked at. The current measures are looked at to see if they can be understood and if they make sense. There are three different intuitive ideas of centrality that have been found, and existing measurements are improved to describe these ideas. For each idea, three measurements are made: one that shows how centralized the network is as a whole, one that shows the absolute and relative number of constituents in a network, and one that shows how many constituents there are in total in a network. Researchers look into what these factors mean for experiments with small groups. Keywords: Clarification Concept of Centrality, Social Networks.